Local Products’ Marketing Strategies to Go International: A Case Study on Erigo - Mutia Sari Dewi; Nuri Aslami (Indonesian Journal of Multidisciplinary Science, 2022)
Developing a product marketing strategy in order to get potential buyers and be able to compete with competitors is a very important thing for a business owner to think about. Even though the resulting product is unique and of good quality, it may not always be in demand by potential buyers. A good marketing strategy must be owned because the right marketing strategy aims to be able to introduce it to the wider community, both local and even overseas. This research model uses a qualitative approach with a document study method. The result of this research is that the CEO of Brand Erigo is very good at carrying out product marketing strategies in 2020 by expanding the reach of markets outside Indonesia through the Shopee export program. Sadad's courage to take a business capital loan and then use it with an effective product marketing strategy, then the Erigo brand successfully goes to America in 2020. This achievement certainly deserves to be an inspiration for local entrepreneurs and MSMEs who are now rising through the pandemic crisis.